Pre-LGM Northern Hemisphere ice sheet topography - J. Kleman; J. Fastook; K. Ebert; J. Nilsson; R. Caballero (Climate of the Past, 2013)
We here reconstruct the paleotopography of Northern Hemisphere ice sheets during the glacial maxima of marine isotope stages (MIS) 5b and 4.We employ a combined approach, blending geologically based reconstruction and numerical modeling, to arrive at probable ice sheet extents and topographies for each of these two time slices. For a physically based 3-D calculation based on geologically derived 2-D constraints, we use the University of Maine Ice Sheet Model (UMISM) to calculate ice sheet thickness and topography. The approach and ice sheet modeling strategy is designed to provide robust data sets of sufficient resolution for atmospheric circulation experiments for these previously elusive time periods. Two tunable parameters, a temperature scaling function applied to a spliced Vostok–GRIP record, and spatial adjustment of the climatic pole position, were employed iteratively to achieve a good fit to geological constraints where such were available. The model credibly reproduces the first-order pattern of size and location of geologically indicated ice sheets during marine isotope stages (MIS) 5b (86.2 kyr model age) and 4 (64 kyr model age). From the interglacial state of two north–south obstacles to atmospheric circulation (Rocky Mountains and Greenland), by MIS 5b the emergence of combined Quebec–central Arctic and Scandinavian–Barents-Kara ice sheets had increased the number of such highland obstacles to four. The number of major ice sheets remained constant through MIS 4, but the merging of the Cordilleran and the proto-Laurentide Ice Sheet produced a single continent-wide North American ice sheet at the LGM.